Hybrid Precursor Engineering of g-C₃N₄ for Enhanced α-Fe₂O₃/g-C₃N₄ Photoanodes in HMF-Assisted Photoelectrochemical Processes - Muhammad Ibadurrohman; Regina Ulibasa; Nadia Mumtazah; Nurfadlih Syahlani (International Journal of Renewable Energy Development, 2026)
The sluggish kinetics of Oxygen Evolution Reaction (OER) is a challenge for the development of efficient photoelectrochemical (PEC) systems for sustainable hydrogen production. In this work, α-Fe₂O₃/g-C₃N₄ photoanodes were prepared from g-C₃N₄ of different precursors (urea, melamine and/or dicyandiamide) to enhance the charge carrier dynamics and light absorption properties. The hybrid precursor engineered g-C₃N₄ play a key role to tune the structural, optical and photoelectrochemical properties of the composite photoanodes. The as prepared composite with g-C₃N₄ prepared from ternary hybrid precursors (urea, melamine and dicyandiamide) showed the best performance among the as prepared samples with lowest onset potential (0.01 V) and highest ΔE (0.88 V) indicating improved energy efficiency. The enhanced photocurrent density was attributed to the improved charge separation which was verified by the photoluminescence analysis indicating the decreased recombination. Furthermore, the addition of 5-hydroxymethylfurfural (HMF) as a model organic substrate increased the photocurrent density (~95%) with no change in the onset potential, demonstrating the excellent hole scavenging ability of the HMF. Chronopotentiometry measurements confirmed stable operation over long periods of illumination. These results suggest that hybrid precursor engineering in g-C₃N₄ and HMF-assisted PEC systems is a promising strategy to improve the photoelectrochemical performance.